THE INFLUENCE OF CARDIAC RESYNCHRONIZING THERAPY ON VEGETATIVE HEART RHYTHM REGULATION IN INDIVIDUALS WITH CONGESTIVE HEART FAILURE - V. A. Kuznetsov; P. V. Shebeko; T. N. Enina; N. N. Melnikov (Российский кардиологический журнал, 2014)
Aim. To study the influence of cardiac resynchronizing therapy (CRT) on autonomous cardiac regulation during follow-up in patients (pts) with chronic heart failure (CHF).Material and methods. 22 pts (14 (63,6%) males, mean age 50±10,0 years) with implanted cardiac resynchronization devices were examined. 14 (63,6%) pts had ischemic cardiomyopathy, 12 pts (54,6%) were in NYHA class II, 6(27,3%) – III, 4(18,1%) – IV. Mean follow-up was 12,5 [9,3;13,3] months. Heart rate variability (HRV) analysis was performed on 5-minute ECG recordings made at rest and in active orthostatic test (AOT). Echocardiographic and electrocardiographic parameters were estimated. Pts with a decrease in left ventricular end-systolic volume ≥15% was classified as responders (n=11 – gr.I) and <15% – nonresponders (n=11 – gr. II).Results. At baseline in gr.II higher pulmonary artery systolic pressure (PASP) and right ventricle dimension were detected. At baseline in gr.I significant LF/HF increase, SDNN and TP decrease in AOT were observed. During prospective study in gr.I LF/HF increase in AOT was significant and LF and LF% were higher as compared with initial. At baseline and during follow-up in gr.II HRV parameters were unchanged.Conclusion. CRT exerts positive influence on autonomic cardiac regulation in CHF patients. Preservation of sympathetic reactivity in AOT probably can be used as a marker of a good CRT response.